The effect of post-circumcision mucosal cuff length on premature ejaculation - Ongun, Sakir; Dursun, Murat; Egriboyun, Sedat (Canadian Urological Association Journal, 2020)
Introduction: We aimed to compare the length of mucosal cuff after circumcision in patients with and without a complaint of premature ejaculation (PE). Methods: Sexually active patients without erectile dysfunction that presented to the urology polyclinic between March 2018 and June 2018 were included in this multicentered, prospective study. The circumcision age of the patients, the person who performed the procedure (surgeon, non-surgeon), penile length, and dorsal and ventral penile measurements were recorded and compared between patients with and without PE. Results: A total of 208 patients were included in the study. The mean circumcision age of the patients was 5.7±4.2 years, and the mean dorsal and ventral mucosal sizes were 15.02±4.58 mm and 16.31±4.92 mm, respectively. PE was present in 106 of the participants. There was no statistically significant difference between the PE and non-PE groups in terms of the person who performed the procedure (surgeon, non-surgeon). However, patients with PE had statistically significantly longer dorsal and ventral mucosal measurements compared to those without PE (p<0.001). Conclusions: Our study showed that the dorsal and ventral lengths of mucosal tissue left behind after circumcision are a risk factor for PE. Therefore, special attention should be paid not to leave redundant dorsal and ventral mucosal tissue during this procedure.